Contributions of Bacău to the economic literature and culture – The life and work of Professor Vasile Pătruţ - Deju, Mihai (Studies and Scientific Researches. Economics Edition, 2012)
The economic culture and accounting theory in Bacău area has its beginnings in the setting up of the first practical school of agriculture, by Ion Ionescu de la Brad, who included in the curriculum an accounting course, as well. Over the years, the economic education of Bacău area education has evolved from “The School of Accounting and Co-operative Education” (1919) to the modern economic higher education, in our days. During an important period of the evolution of education and culture in Bacău area, Professor Vasile Pătruţ is present, having a significant contribution to the accounting theory, teaching and practice in Bacău.